Sustainable Health Model: Increasing Universal Access to Health Services in Remote Areas - Ardenny, Ardenny; Nam, Le Hoang; Tu, Pham Anh (Journal of World Future Medicine, Health and Nursing, 2025)
Access to healthcare services in remote areas remains a significant global challenge, with many populations experiencing disparities in healthcare availability, quality, and affordability. Sustainable health models that ensure universal access to health services are essential for improving public health outcomes in underserved areas. This study investigates the potential for sustainable health models to increase healthcare access in remote regions, focusing on the role of telemedicine, mobile health clinics, and community health workers. The research employs a mixed-methods approach, combining qualitative interviews with healthcare professionals and quantitative data on healthcare access and outcomes in remote communities. The findings indicate that telemedicine platforms have improved healthcare delivery by 40%, while mobile health clinics and trained community health workers have expanded service reach, particularly in geographically isolated areas. Furthermore, community-based health interventions have led to a 30% reduction in preventable diseases in these regions. The study concludes that integrating technology with community-based solutions offers a scalable and effective approach to achieving universal health access in remote areas. However, challenges such as technology infrastructure, resource allocation, and healthcare workforce training need to be addressed to ensure the sustainability of these models.